Land degradation at the southern slopes of Al-Jabal al Akhdar, Libya - Aburas, Murad M.; Yousef, Mohammed S.; Alferjani, Asama S. (Al-Mukhtar Journal of Sciences, 2015)
Land and Soil degradation at the Southern slopes of Al-Jabal Alkhdar was evaluated; soil degradation-related soil properties were measured. The evaluation included: erosion-related soil surface features, soil depth, mechanical analysis of soil particles, bulk density, organic matter, aggregates stability, soil resistance to penetration and infiltration rate. To achieve the study objectives five different sites were chosen: Meseliba; Marawa; Sirat Alia, Grehat and Qasar Mestashi. The field survey showed that the study area is subjected to intensive soil erosion, the area already suffered from degraded plant vegetation, which resulted in increased loss of soil depth. The investigation of productivity-related soil properties showed a noticeable level of soil degradation in Qasar Mestashi soils compared to the other sites. This can be illustrated by its shallow soil depth which is less than 12.5 cm compared to more than 16 cm at most of the other sites. Organic matter content was 0.39 % compared to more than 1% at the other sites. Clay content and aggregate stability > 2 mm were relatively lower at Qasar Mestashi site compared to the other sites. A low infiltration rate of only 0.03 mm\min indicated the deterioration of soil structure at Qasar Mestashi site. A relative increase in soil resistance to penetration and bulk density were also found and may have contributed to soil degradation. The shallow soil depth will always be a major obstacle preventing the return of balance to this fragile ecosystem. The application of soil conservation measures would improve soil depth and its holding capacity, which are needed to enhance plant cover.